SCREENING AND EVALUATION OF ANTIMICROBIAL AGENTS FROM FUNARIA SP. AGAINST VARIOUS PATHOGENS - Chauhan, Ritika; Navlekar, Anisha; Ghosh, Enoch; Abraham, Jayanthi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The present study was carried out to evaluate the biological active phytochemical compounds from moss of Berijam Lake, Kodaikanal, India. Methods: Acetone and methanol extracts of moss were obtained using soxhlet extractor and the obtained extracts were evaluated for various biological activities. The combined effect of commercially available antibiotics and moss extracts was also investigated by disk-diffusion assay method against various Gram positive and Gram negative bacteria. The free radical scavenging activity of moss extracts were studied by 2,2-diphenyl-1-picrylhydrazyl (DPPH). Results: The maximum zone of inhibition was found against Gram negative pathogens whereas weak inhibitory activity was investigated against Staphylococcus aureus. The combined effect of chloramphenicol with acetone and methanol extracts exhibited pronounced antimicrobial effect against Bacillus subtilis, Proteus mirabilis and Escherichia coli. The phytochemical tests revealed the presence of carbohydrates in Funaria sp. and the acetone extract showed effective antioxidant activity when compare to methanol extract using free radical scavenging assay. Conclusion: The present study reveals that the bryophytes from Berijam Lake possess potential antimicrobial and antioxidant activity. Keywords: synergistic effect, bryophytes, clinical pathogens, antibiotics